A reference requirements set for public service provision enterprise architectures - Tambouris, Efthimios; Kaliva, Eleni; Liaros, Michail; Tarabanis, Konstantinos (Software and systems modeling, 2014)
Electronic Government (eGov) is a political priority worldwide. One of the core objectives of eGov is the online public services provision (PSP). However, many of eGov PSP systems fail in realizing their objectives. Enterprise Architectures (EA) could contribute to overcome some of the relevant obstacles. The objective of this paper is to derive a reference requirements set for eGov PSP that can be used in EA development. Aiming at capitalizing on existing knowledge, we conduct a systematic literature review on eGov PSP systems requirements. This results in identifying a unified requirements set, i.e. 186 requirements, and stakeholders set, i.e. 19 stakeholders, for eGov PSP systems. Based on these findings, we determine 16 overview use cases demonstrating the basic functionality of such systems. Our findings are modeled using ArchiMate 2.0 notation. The identified requirements set can be used by virtually any public organization providing public services for developing its own EA. As a result, it can lead to the reduction of eGov PSP project failures, the decrease of software development costs and the improvement of its effectiveness and quality. Furthermore, it can be used as a basis to develop a complete reference EA for the eGov PSP domain.